2005
DOI: 10.1002/macp.200500260
|View full text |Cite
|
Sign up to set email alerts
|

Poly[(4‐hydroxybutyric acid)‐alt‐(glycolic acid)]: Synthesis by Thermal Polycondensation of Metal Salts of 4‐Chlorobutyric Acid Carboxymethyl Ester

Abstract: Summary: A new sequential copolyester consisting of glycolic acid and 4‐hydroxybutyric acid units was prepared by a thermal polycondensation method that uses the formation of metal chloride salts as a driving force. The polymerization conditions (time, temperature) were studied in order to obtain appropriate molecular weights and high yields. Thermal properties and thermal stability were also determined. The polymerization kinetics of sodium, potassium and cesium monomer derivatives were studied by differentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 29 publications
(40 reference statements)
1
12
0
Order By: Relevance
“…Poly(4Hb‐ alt ‐Glc) was synthesized with an 80% yield by thermal polyesterification of the potassium salt of 4‐chlorobutyric acid carboxymethyl ester, as previously reported12 (Scheme ). The intrinsic viscosity measured in dichloroacetic acid at 25 °C was 0.46 dL/g.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Poly(4Hb‐ alt ‐Glc) was synthesized with an 80% yield by thermal polyesterification of the potassium salt of 4‐chlorobutyric acid carboxymethyl ester, as previously reported12 (Scheme ). The intrinsic viscosity measured in dichloroacetic acid at 25 °C was 0.46 dL/g.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we have demonstrated that this kind of thermal polycondensation reaction is especially useful for preparation of alternating poly(ester amide)s containing glycolic acid units 10, 11. This procedure has also been extended to the production of alternating polyesters such as those derived by polymerization of Cl(CH 2 ) 3 COOCH 2 COO − K + and ClCH 2 COO(CH 2 ) n −1 COO − K + monomer salts 12. In this way, it is possible to obtain a set of biodegradable materials whose properties can be tuned by changing the number of methylene groups of the glycolic acid comonomer.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, if we accept that, as confirmed by many experimental data reported in the published literature [3][4][5], there exists a linear correlation between the standard activation enthalpies and entropies for a family of related chemical reactions (differing usually either in the inert substituent of one of the reactants, provided that this is an organic species, or in the solvent used): plot, respectively, we must also accept (and confirmed by experimental results [6]) that there also exists a linear correlation between the Arrhenius parameters that can be expressed as: …”
Section: Introductionmentioning
confidence: 99%
“…Poly(Glc‐ alt ‐6HH) was synthesized by the thermal polyesterification of the potassium salt of 6‐(2‐chloroacetate)hexanoic acid, as previously reported,13 with an 80% yield [Scheme (a)]. Poly(4Hb‐ alt ‐Glc) was synthesized by the thermal polyesterification of the potassium salt of 4‐chlorobutyric acid carboxymethyl ester, as previously reported,12 with an 80% yield [Scheme (b)].…”
Section: Methodsmentioning
confidence: 99%